PEMBELAJARAN TARI REBANA PADA SANGGAR TARI KREASI SENJA DI KECAMATAN SELO KABUPATEN BOYOLALI - Dwi Rahmani (Institut Seni Indonesia Surakarta, 2016)
The activity of dance training is the continuation of the third Tri Dharma Perguruan Tinggi (The Institution Three Dharma) that is community service and it is one of the teacher s tasks as well as obligation. The teachers of Dance Department in Institut Seni Indonesia (ISI) Surakarta hold the program and they hope it will become a continuous activity as a media for increasing traditional arts being. Besides that, it is also a mediafor teachers to publish the Institution. Finally, the program is supposed to be able to significantly affect input qualitatively as well as quantitatively. The activity will be leaded to the learning of creative traditional dance, Rebana, for the students in Studio Kreasi Senja, Selo, Boyolali. They are also students in SMKN I Selo Boyolali. The expectation of the program is that students can present Rebana dance. The object of the program is students of SMKN I Selo Boyolali that are also joined in Senja Creative Dance Studio, Selo, Boyolali, especially for the extracurricular activity, dance. The learning method used in this activity includes speech, demonstration, and drilling. The result will be a repertoire of creative traditional dance called Rebana completed by make up and customs.Key words : creative traditional dance, dance learning, appreciation